CO-CREATING DIGITAL SOLUTIONS: EMPOWERING TRADITION THROUGH PARTICIPATORY ACTION RESEARCH - Rambukwelle, H.M.R.O.B. (University of Vavuniya, 2025)
This Participatory Action Research (PAR) project sought to improve the digital presence and customer engagement of Maruthu Dum Biryani, a traditional MSME in Jaffna, by co-creating and implementing low cost digital platforms such as Facebook, Instagram, Google Maps and WhatsApp Business for customer engagement. Over four months, a team of marketing students and the business owner undertook PAR cycles, including diagnosis (survey and digital readiness assessment), action (setting up and improving digital platforms), observation (engagement metrics) and reflection (owner feedback and audience interactions with -creation and trained him in his new role as a social media manager. The business noticed an increase in visibility, the students and owner reported organic customer interactions as a result of implementing planned social media posts and video advertising campaigns. Platforms such as Google Maps and Instagram had a significantly better impact on brand awareness for the owner, as they were given visible actions to strengthen public-facing engagement with these platforms. A notable outcome was that the owner, who was initially hesitant to engage with digital communications, began to feel confident in managing these digital resources. A significant outcome for students, business owners, and MSME employees was improved levels of digital literacy demonstrated in aspects of productivity, content creation, engagement analytics, and customer engagement. The study highlights the power of student-MSME partnerships to foster digital empowerment in low-resource settings, providing a practical, replicable model for other traditional food businesses. It emphasizes a gradual digital transformation approach that starts with one platform and gradually expands. The research recommends that universities establish student-led digital pitch, policymakers encourage mentoring between youth and business owners, and financial institutions provide microloans for essential digital tools. Together, these strategies can preserve local food heritage while helping MSMEs thrive in Sri Lank's growing digital economy.
Keywords: Co-creating; Digital Empowerment; Local Business Transformation; Participatory Action Research; Student-led Digital Pitch